Regulation of energy balance and adiposity: a model with new approaches (Revista Española de Fisiología, 1996)
Obesity etiology and treatment have been fraught with disappointment for researchers, because the mechanisms regulating fuel homeostasis and adiposity are incompletely understood. It can now be hypothesized in the light of new evidences that the control of body weight and composition depends upon an axis with three interrelated and self-controlled components: 1) food intake; 2) nutrient turnover and thermogenesis and 3) body fat stores, all of which underly complex feedback mechanisms. This approach considers two of the most relevant recent findings in the field (leptin and beta 3-adrenoceptors), adding new views to previous metabolic models of obesity. This perspective supplies some additional clues to the understanding of body composition regulation as well as the potential involvement of genetic and hypothalamic disorders in the onset of obesity.